The Welfare of Nile Tilapia (Oreochromis niloticus, GIFT Strain) Juveniles Cultured in Different Light Spectra - Yi, Mengmeng; Zhai, Wanting; Wang, Miao; Wang, He; Liu, Zhigang; Gao, Fengying; Ke, Xiaoli; Song, Changbin; Cao, Jianmeng; Lu, Maixin (Frontiers in Marine Science, 2022)
The light spectrum is a vital environmental factor for the culture of fish, and the welfare of farmed fish is a crucial issue in aquaculture. In this study, Nile tilapia (Oreochromis niloticus, GIFT strain) juveniles were exposed to full-spectrum (LW), red (LR), yellow (LY), or blue (LB) light. After the 45-day experiment, growth performance, stress responses, and aggressive behaviors were evaluated, and transcriptomic analysis was carried out. The results revealed that LW and LR positively affected growth performance. At the same time, LY and LB had a negative effect. Light spectrum induced stress responses of juvenile fish exposed to LY, under which the total antioxidant capacity (T-AOC) and cortisol (COR) contents were the highest. The activities of α-amylase (AMS), protease (PES), and lipase (LPS) in the digestive tract showed a similar tendency, indicating that the light spectra altered the digestive enzyme activities and then affected growth. Behavioral analyses showed increased chase and bite activities of tilapia juveniles exposed to LW and LY. The affected functions included the nervous system, muscle morphogenesis, and immune system-related regulation. Enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways include the tryptophan metabolism signaling pathway, protein digestion and absorption signaling pathway, Jak-STAT signaling pathway, arachidonic acid metabolism signaling pathway, and alpha-linolenic acid metabolism signaling pathway. Overall, light spectra influenced the welfare of farmed tilapia juveniles in terms of growth, stress, and behavior. Our results suggested that LR should be used in juvenile tilapia culture.